Education for Youth and Adults: enchantment and permanency at school - Fiss, Dóris Maria Luzzardi; Machado, Jeferson Ventura (Education Policy Analysis Archives, 2014)
This research, conducted in 2011 and 2012, tried to identify the factors of student retention and enchantment with the school, valuing situations that reduce the effects of the processes of exclusion in EJA (Education for Youth and Adults. Considering a complex situation in which rivaling dropout and permanency, it was asked: What makes this learner stay at school? What happens during their journey that makes them keep their bound with the institution? Paulo Freire, Fernando Luís Monteiro Miletus, Gerson Tavares do Carmo and Juarez were Dayrell theoretical references. Empirical work included interviews of ninety students at a local public school (Porto Alegre, Rio Grande do Sul, Brazil). It was concluded that most of the students interviewed EJA looking at this school, were motivated by the need for social mobility, knowledge or certification. The factors, which determine effective permanency, are articulated as the desire of social group belonging or the relevance or to the meaning of learnt subjects.